Analysis of Feed and Medicine Communication Network in Karapan Cattle Conservation Community in Sampang - Sukisno, Safira Amalia; Padmaningrum, Dwiningtyas; Suminah, Suminah (Jurnal Komunikasi, 2023)
An accurate analysis of the communication network will facilitate the process of disseminating information about feed and medicines. This study aims to analyze the roles, identify clicks, and analyze the structure of the communication network for feed and medicines formed among conservationists of karapan cattle in Sampang Regency. This study uses a quantitative method with descriptive analysis. The sampling method uses the snowball sampling method. The respondents of this study were 26 conservationists of Karapan cattle in Sampang Regency. The data analysis method used in this research is sociometric analysis. The results of the study show that: (1) the feed and medicine communication network in Sampang Regency has the roles of opinion leaders, bridges, and neglectees; (2) the clicks generated in the feed communication network are 20 clicks, while the clicks contained in the drug communication network are 4 clicks; (3) the pattern of the feed communication network is all channels and wheels while the pattern of the drug communication network is wheels. The density value in the feed communication network is 0.128 which is higher than the drug communication network which is 0.057. The diameter formed in the feed communication network is 6 while in the drug communication network it is 5, which means that the farthest distance a conservationist can contact other conservationists in the feed communication network is 6 steps while in the drug communication network it is 5 steps. The degree of connectedness in the feed communication network was 89.4%, lower than the drug communication network of 24.9%, indicating that the dissemination of feed information was better than the dissemination of information about medicines.